Рееміґрація кримських татар у 1860-х рр. - Алієв, Р.Д. (Український історичний журнал, 2014)
Розглядається маловідомий епізод історії кримськотатарського народу, пов’язаний із рееміґрацією з Османської імперії, що розпочалася в 1860-х рр., майже відразу після масового виїзду з Криму. Дається оцінка відповідних заходів адміністрації Таврійської ґубернії. The article regards one of the less known episodes in history of Taurian province – remigration of Crimean Tatars from the Ottoman Empire territories in 1860th. The author made an attempt to analyze main questions of the research. Based on the archive files and historical researches the article gives detailed evaluation of Province governance actions according to the problem.